Penerapan Pendidikan Karakter Dalam Meningkatkan Hasil Belajar Siswa Di SD Al Ma'some - Roufatunnur; Elya Umi Hanik; Siti Durotun Naviroh; Erma Novita; Selvy Wahyuni (Arus Jurnal Pendidikan, 2021)
This writing aims to learn about the application of discipline character values in improving student learning outcomes at Al-Ma'soem Elementary School Bandung. This writing uses descriptive qualitative research methods in obtaining data. So as to be able to explain the process of applying discipline character values that can improve student learning outcomes. The population of this study were students and educators of SD Al-Ma'soem. Based on the results of the study, it was found that the value of the character of discipline was obtained consistently with time and things that could realize the potential of students. This is inseparable from the teacher's role as characterforming in students by habituation of living disciplined attitudes, behavior, and ethics in the learning process at school. Thus, this writing is expected to form the character of self-discipline in students so that they are able to improve learning outcomes in a better direction.